1986
DOI: 10.1002/jcb.240320202
|View full text |Cite
|
Sign up to set email alerts
|

Viral therapy: Prospects for protease inhibitors

Abstract: Antiviral activities of known protease inhibitors were assayed in virus-infected cell cultures. Some members of the cystatin superfamily, in particular chicken cystatin, were able to block virus replication. In a binding assay, using purified components, chicken and human cystatin were able to bind poliovirus protease with affinities which were reflected in their relative antiviral potencies. Prospects for application of protease inhibitors in clinical viral infections are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 8 publications
2
30
0
Order By: Relevance
“…Table I shows the inhibition of the viral CPE by various cysteine proteinase inhibitors. OC-I and OC-II are apparently potent antiviral agents against poliovirus at a concentration of 8 nmol/ml, similar to the inhibitory effect of egg white cystatin reported previously [6]. The truncated oryzacystatin-I mutant, tOC-I, is also effective.…”
Section: Febs Le'frerssupporting
confidence: 83%
See 1 more Smart Citation
“…Table I shows the inhibition of the viral CPE by various cysteine proteinase inhibitors. OC-I and OC-II are apparently potent antiviral agents against poliovirus at a concentration of 8 nmol/ml, similar to the inhibitory effect of egg white cystatin reported previously [6]. The truncated oryzacystatin-I mutant, tOC-I, is also effective.…”
Section: Febs Le'frerssupporting
confidence: 83%
“…If internalized, therefore, cystatins, a family of proteinaceous cysteine proteinase inhibitors, might be excepted to inhibit the replication of picornaviruses in infected cells. In fact, egg white cystatin has been shown to exhibit this type of inhibitory action [6]. Recently, cystatin C, which exists in human blood, tears and bone marrow, has also been reported to have an antiviral effect against herpesvirus [7].…”
Section: Introductionmentioning
confidence: 99%
“…High concentrations of stefin A selectively localized Table 1 Inhibition constants (Ki,,,) [23,24]. There is an abundance of stefin A mRNA in chemically induced mouse skin papillomas but a decrease in mRNA with progression to carcinomas [8].…”
Section: Discussionmentioning
confidence: 99%
“…Sphingosine and Hl histone in the epidermis have been reported to have antimicrobial and antifungal activities [17,18]. However, proteinase inhibitors have also been reported to have antiviral, antimicrobial, and antifungal activities [5][6][7]19,20]. Moreover, it is well known that Staphylococcus aureus is increased on the skin surface of the lesions of atopic dermatitis.…”
Section: I3i!xxdonmentioning
confidence: 99%
“…Korant et al [5,6] reported that egg white cystatin inhibited the cysteine proteinase of the picoma virus and inhibited the processing of the virus precursor protein. It was found that the replication of Herpes simplex was blocked by cystatin C [7].…”
Section: Introductionmentioning
confidence: 99%